Old and New Perspectives on Mortality Forecasting - Bengtsson, Tommy; Keilman, Nico.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This open access book describes methods of mortality forecasting and discusses possible improvements. It contains a selection of previously unpublished and published papers, which together provide a state-of-the-art overview of statistical approaches as well as behavioural and biological perspectives. The different parts of the book provide discussions of current practice, probabilistic forecasting, the linearity in the increase of life expectancy, causes of death, and the role of cohort factors. The key question in the book is whether it is possible to project future mortality accurately, and if so, what is the best approach. This makes the book a valuable read to demographers, pension planners, actuaries, and all those interested and/or working in modelling and forecasting mortality.".
Ch 1.Introduction: Tommy Bengtsson, Nico Keilman, Juha Alho, Kaare Christensen, Edward Palmer, James W. Vaupel: SECTION 1. Current practice: Introduction by Tommy Bengtsson and Nico Keilman -- Ch 2. Life Expectancy is Taking Center Place in Modern National Pension Schemes - A New Challenge for the Art of Projecting Mortality: Edward Palmer -- Ch 3. Experiences from Forecasting Mortality in Finland: Juha Alho -- Ch 4. Mortality Projections in Norway: Helge Brunborg -- Ch 5. Mortality Assumptions for Sweden. The 2000-2050 Population Projection: Hans Lundström -- Ch 6. Forecasting Life Expectancy: The SCOPE Approach: James W. Vaupel -- Ch 7. Mortality Forecasts. Comments on How to Improve Existing Models - an Epidemiologist's Perspective: Kaare Christensen -- Ch 8. The Need for Looking Far Back in Time When Predicting Future Mortality Trends: Tommy Bengtsson -- SECTION 2. Probabilistic models: Introduction by Nico Keilman -- Ch 9. Erroneous Population Forecasts: Nico Keilman -- Ch 10. Remarks on the Use of Probabilities in Demography and Forecasting: Juha M. Alho -- Ch 11. An Expert Knowledge Approach to Stochastic Mortality Forecasting in the Netherlands: Maarten Alders and Joop de Beer -- Ch 12. Stochastic Forecasts of Mortality, Population and Pension Systems: Shripad Tuljapurkar -- SECTION 3. The linear rise in life expectancy: History and prospects: Introduction by Tommy Bengtsson -- Ch 13. The Linear Rise in the Number of Our Days: Jim Oeppen and James W. Vaupel -- Ch 14. Mortality Forecasts and Linear Life Expectancy Trends: Ronald Lee -- Ch 15. Forecasting Life Expectancy: A Statistical Look at Model Choice and Use of Auxiliary Series: Juha M. Alho -- Ch 16. Life Expectancy Convergence among Nations since 1820: Separating the Effects of Technology and Income: Jim Oeppen -- Ch 17. Linear Increase in Life Expectancy: Past and Present: Tommy Bengtsson -- SECTION 4. Causes of death: Introduction by Tommy Bengtsson and Kaare Christensen -- Ch 18. How Useful Are the Causes of Death When Extrapolating Mortality Trends. An Update: Graziella Caselli, Jacques Vallin and Marco Marsili -- Ch 19. Forecasting Life Expectancy and Mortality in Sweden - Some Comments on Methodological Problems and Potential Approaches: Måns Rosén -- Ch 20. How Analysis of Mortality by Cause of Death is Currently Influencing UK Forecasts: Richard Willets -- SECTION 5. Cohort factors: How conditions in early life influence mortality later in life: Introduction by Tommy Bengtsson -- Ch 21. A Life Course Perspective to the Modern Secular Mortality Decline and Socioeconomic Differences in Morbidity and Mortality in Sweden: Martin Lindström and George Davey Smith -- Ch 22. Early Life Events and Later Life Health: Twin and Famine Studies: Kaare Christensen -- Ch 23. The Month of Birth: Evidence for Declining but Persistent Cohort Effects in Lifespan: Gabriele Doblhammer -- Ch 24. Early-Life Conditions and Old-Age Mortality in a Comparative Perspective:19th Century Sweden and Belgium: Tommy Bengtsson and George Alter. .
Keywords: Demography; Population; Population -- Economic aspects; Social sciences -- Statistical methods; Population and Demography; Population Economics; Statistics in Social Sciences, Humanities, Law, Education, Behavorial Sciences, Public Policy